Lophosceles Ringdahl 1922 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Lophosceles Ringdahl, 1922 Lophosceles Ringdahl, 1922: 3. Type-species: Musca mutata Fallén, 1825, by original designation. Lophosceles cinereiventris (Zetterstedt, 1845) Aricia cinereiventris Zetterstedt. 1845: 1500. Type-locality: Sweden, Jämtland, Skalstugan. Holotype ♂, MZLU (Pont, in press). Siberian records: Respublika Altay (Sorokina, 2006b: 139). General distribution: Holarctic Region; in the Palaearctic, from Europe east to China. Lophosceles frenatus (Holmgren, 1872) Aricia frenatus Holmgren, 1872: 103. Type-locality: not stated (from title: Nordgrönland, actually N W Greenland, Nordfjord). Syntypes 2♂, NHRS (seen). Siberian records: Pripolar Urals, Mt. Neroika (Malozemov, 1992: 92). General distribution: Holarctic Region; in the Palaearctic, from montane and northern Europe, Russia (north-west European Russia, West Siberia) and China. Lophosceles hians (Zetterstedt, 1838) Anthomyza hians Zetterstedt, 1838: 698. Type-locality: Finland, Lapland, Muonioniska. Lectotype ♀, MZLU (designated by Pont, in press). Siberian records: West Siberia (Pont, 1986a: 135). General distribution: Holarctic Region: Northern Europe, Russia (north-west European Russia, West Siberia) and Alaska. Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on page 40, DOI:10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926